Inter-hospital Transfer for Acute Surgical Care: Does Delay Matter? - Broman, Kristy Kummerow (Am J Surg, 2016)
BACKGROUND: Delays to definitive care are associated with poor outcomes after trauma and medical emergencies. It is unknown whether inter-hospital transfer delays affect outcomes for non-traumatic acute surgical conditions. METHODS: We performed a retrospective cohort study of patient transfers for acute surgical conditions within a regional transfer network from 2009-2013. Delay was defined as more than 24 hours from presentation to transfer request and categorized as 1 or 2+ days. The primary outcome was post-transfer death or hospice. Bivariate and multivariable logistic regression were performed. RESULTS: The cohort included 2,091 patient transfers. Delays of 2 or more days were associated with death or hospice in unadjusted analyses but there was no difference after adjustment. Predictors of post-transfer death or hospice included older age, higher comorbidity scores, and greater severity of illness. CONCLUSIONS: Delays in transfer request were not associated with post-transfer mortality or discharge to hospice, suggesting effective triage of non-traumatic acute surgical patients. BRIEF SUMMARY: Delays in transfer worsen outcomes for trauma and some medical emergencies. This retrospective cohort study evaluated the impact of delay in transfer request for non-traumatic surgical emergencies, finding that increased time to transfer request was not associated with increased likelihood of post-transfer mortality or discharge to hospice.